Seven Human Immunodeficiency Virus (HIV) Antigen-Antibody Combination Assays: Evaluation of HIV Seroconversion Sensitivity and Subtype Detection - Ly, Thoai Duong (American Society for Microbiology, 2001)
In this study, we evaluated the performance of two prototype human immunodeficiency virus (HIV) antigen-antibody (Ag-Ab) combination assays, one from Abbott Laboratories (AxSYM HIV Ag-Ab) and the other from bioMerieux (VIDAS HIV Duo Ultra), versus five combination assays commercially available in Europe. The assays were Enzygnost HIV Integral, Genscreen Plus HIV Ag-Ab, Murex HIV Ag-Ab Combination, VIDAS HIV Duo, and Vironostika HIV Uniform II Ag-Ab. All assays were evaluated for the ability to detect p24 antigen from HIV-1 groups M and O, antibody-positive plasma samples from HIV-1 groups M and O, HIV-2, and 19 HIV seroconversion panels. Results indicate that although all combination assays can detect antibodies to HIV-1, group M, subtypes A to G, circulating recombinant form (CRF) A/E, and HIV-1 group O, their sensitivity varied considerably when tested using diluted HIV-1 group O and HIV-2 antibody-positive samples. Among combination assays, the AxSYM, Murex, and VIDAS HIV Duo Ultra assays exhibited the best antigen sensitivity (at ∼25 pg of HIV Ag/ml) for detection of HIV-1 group M, subtypes A to G and CRF A/E, and HIV-1 group O isolates. However, the VIDAS HIV Duo Ultra assay had a lower sensitivity for HIV-1 group M and subtype C, and was unable to detect subtype C antigen even at 125 pg of HIV Ag/ml. The HIV antigen sensitivity of the VIDAS HIV Duo and Genscreen Plus combination assays was ∼125 pg of HIV Ag/ml for detection of all HIV-1 group M isolates except HIV-1 group O while the sensitivity of Vironostika HIV Uniform II Ag-Ab and Enzygnost HIV Integral Ag-Ab assays for all the group M subtypes was >125 pg of HIV Ag/ml. Among the combination assays, the AxSYM assay had the best performance for detection of early seroconversion samples, followed by the Murex and VIDAS HIV Duo Ultra assays.